Penilaian Postur Kerja Dan Keluhan Musculoskeletal Disorders (Msds) Pada Pekerja Back Office di Hotel XY Yogyakarta - Fina Nova Sa’diyah; Moch Sahri; Ratna Ayu Ratriwardhani; Merry Sunaryo (Peneliti.net, 2022)
Musculoskeletal disorders (MSDs) are disorders of the soft tissues (muscles, joints, ligaments, cartilage) and the nervous system of workers. The risk of MSDs can be found in work activities, one of which is the back office, where 80% of work activities are carried out in sitting, standing, squatting, and bending work postures for 1 working day (8 hours). The purpose of this study was to analyze work posture and complaints of musculoskeletal disorders (MSDs) in back office workers.This research is a descriptive quantitative research using an observational approach. The population in this study amounted to 25 workers from both the Finance and Engineering departments at Hotel XY Yogyakarta. The sampling technique in this study is to use a total sampling technique. Collecting data in this study by taking samples of Musculoskeletal Disorders (MSDs) complaints using a Nordic Body Map (NBM) questionnaire and for work postures using the Ovako Working Analysist System (OWAS) method.The results of the study were obtained from the percentage of 44% in the low category and the total percentage of 56% of the MSDs risk value in the moderate category with that the need to make efforts to control or improve work position or posture in the future and from the results of the assessment (Ovako Work Posture Analysis System) OWAS obtained activity work with uncomfortable work postures, so it is necessary to improve the work posture of workers.Conclusions from the results and discussion have complaints about the level of risk of Musculuskeletal Disorders (MSDs) and work postures. So the advice that can be given is the need to improve an ergonomic work position, stretch the muscles on the sidelines of working hours and take a short break during breaks